Choroidal neovascular membrane characteristics in Age-Related Macular Degeneration: Insights from Angiography and Optical Coherence Tomography - Shakya, Kiran; Ranabhat, Sudha; Dhungana, Arun Prasad; Shakya, Sangita (Journal of Advanced Academic Research, 2025)
Background: Choroidal neovascular membrane (CNVM) is common problems and causes loss of central sight in the geriatric population. This is essential to comprehend the morphological characteristics of CNVM and baseline visual acuity (VA) in age-related macular degeneration (AMD). Objective: To examine the correlation between new patients with untreated AMD and their baseline VA, demographic, angiographic, and spectral-domain OCT (SD-OCT) CNVM features. Methods: A study was conducted at a tertiary eye hospital on 50 eyes belonging to consecutive individuals with newly diagnosed and untreated AMD from June 2022 to May 2023. Snellen baseline visual acuity (VA) was converted to the LogMAR scale. SD-OCT biomarkers were meticulously study for intraretinal fluid (IRF), subretinal fluid (SRF), sub-RPE fluid (SRPE), hyperreflective material (HRM), photoreceptor disruption, hyperreflective foci (HRF), and Outer retinal tubulation (ORT). OCT angiography helped to find choroidal neovascular membrane type and location. Results: In this study, 28 (56%) of the participants in this study were male, and the mean age was 73.3 ± 8.7 years. The baseline visual acuity VA) score in this study was 1.06±0.38 Log MAR. Visual acuity was observed to be considerably lower when SRF (p=0.01) and SRPE (p=0.03) were present. Age, sex, CNVM types, lesion pattern, and the presence of IRF, HRM, photoreceptor disruption, ORT, or HRF did not significantly correlate with BCVA. Conclusion: In the untreated AMD, the presence of SRF and SRPE fluid on SD-OCT were significant biomarkers for worse baseline visual function. In contrast, CNVM type and other OCT biomarkers showed no significant association with initial visual acuity.